2020
DOI: 10.1111/bpa.12841
|View full text |Cite
|
Sign up to set email alerts
|

B cell rich meningeal inflammation associates with increased spinal cord pathology in multiple sclerosis

Abstract: Increased inflammation in the cerebral meninges is associated with extensive subpial cortical grey matter pathology in the forebrain and a more severe disease course in a substantial proportion of secondary progressive multiple sclerosis (SPMS) cases. It is not known whether this relationship extends to spinal cord pathology. We assessed the contribution of meningeal and parenchymal immune infiltrates to spinal cord pathology in SPMS cases characterized in the presence (F+) or absence (F−) of lymphoid-like str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 59 publications
9
94
0
Order By: Relevance
“…As B cells are most prominent in the meninges of both MS2 patients and 2 month CMI animals, this would suggest that at first T cells and myeloid cells populate the MS meninges, with the amount of meningeal B cells rising over time. This also fits with the finding that the amount of B cells in meninges and B-cell related cytokines in the CSF associate with disease progression 17,28,33 . Furthermore, the extent of meningeal inflammation in MS patients, and more specifically the amount of meningeal B cells, has been strongly linked to the presence of tertiary lymphoid-like follicles 15,28 .…”
Section: Discussionsupporting
confidence: 88%
“…As B cells are most prominent in the meninges of both MS2 patients and 2 month CMI animals, this would suggest that at first T cells and myeloid cells populate the MS meninges, with the amount of meningeal B cells rising over time. This also fits with the finding that the amount of B cells in meninges and B-cell related cytokines in the CSF associate with disease progression 17,28,33 . Furthermore, the extent of meningeal inflammation in MS patients, and more specifically the amount of meningeal B cells, has been strongly linked to the presence of tertiary lymphoid-like follicles 15,28 .…”
Section: Discussionsupporting
confidence: 88%
“…A cellular infiltrate suggestive of inflammatory activity was only detected in 3 of 154 blocks of our sample. Evidence suggests the main signature of inflammation in the spinal cord may be located in the meninges, 33 which were not examined in this study. Although inflammation may contribute to synaptic damage/loss in the course of MS, it may not necessarily be involved in the initiation of the processes leading to connectivity breakdown in the spinal cord.…”
Section: Discussionmentioning
confidence: 83%
“…One theory supporting a key role of inflammation in subpial cortical pathology, while reconciling pathological and clinical findings of progressive MS, proposes that this injury may be driven by a compartmentalized immune response involving the inflamed leptomeninges within brains that have a relatively intact BBB (Serafini et al, 2004;Lassmann et al, 2007;Magliozzi et al, 2007Magliozzi et al, , 2010Howell O. W. et al, 2011;Lucchinetti et al, 2011;Popescu et al, 2011;Choi et al, 2012;Absinta et al, 2015;Howell et al, 2015;Haider et al, 2016). Histological examination of autopsy CNS tissue from progressive MS cases have shown evidence of Tertiary Lymphoid Tissues (TLT) in the leptomeninges lining the forebrain (Serafini et al, 2004;Magliozzi et al, 2007), the cerebellum (Howell et al, 2015) and to a lesser extent the spinal cord (Reali et al, 2020). MRI studies have also confirmed the presence of meningeal TLT in the MS brain (Absinta et al, 2015).…”
Section: Ms Gray Mattermentioning
confidence: 99%